If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45.9 = 170 * 0.09t Multiply 170 * 0.09 45.9 = 15.3t Solving 45.9 = 15.3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-15.3t' to each side of the equation. 45.9 + -15.3t = 15.3t + -15.3t Combine like terms: 15.3t + -15.3t = 0.0 45.9 + -15.3t = 0.0 Add '-45.9' to each side of the equation. 45.9 + -45.9 + -15.3t = 0.0 + -45.9 Combine like terms: 45.9 + -45.9 = 0.0 0.0 + -15.3t = 0.0 + -45.9 -15.3t = 0.0 + -45.9 Combine like terms: 0.0 + -45.9 = -45.9 -15.3t = -45.9 Divide each side by '-15.3'. t = 3 Simplifying t = 3
| -101=4x+5x+7 | | 36-4k+2=6(-9k-13) | | 6(5y-7)=7(4y-10) | | 5(x+3)-7=8 | | 10.8=0.9n | | x^2+400=625 | | 9m-(4m-8)=-53 | | X^2+3.99X-0.004=0 | | 5x+15=5x+5 | | 7x-31=4+5 | | -12m-3m=0 | | x^2+6x+y^2+8y=16 | | 2/3a=12 | | B/14-4=-2 | | 2=3x+6x-7 | | 4x^2-12x+x=0 | | 290/-4 | | 1/4s=-6 | | ((c/(c+4))+(3/5c))/((c/(9c+36))+3/c) | | 4x-3+12x=6x-33 | | 61y=15(4y+27) | | 7=-4x+2x-3 | | (x^2-6x+8)/(x^2-5x+6) | | 7x+9+8x-7=3x+12x-1 | | 2(5+3x)=4(2x) | | 0.9-200/x^2=0 | | 9a+7=81-a | | 1/4z=-9 | | 2(5y-2)=8y | | 6x+5=4x+51 | | -34=3d+8(3) | | 7x+9+8x-7=3x+12-1 |